Digital Khitbah Among Muslims: The Legality and Ethical Challenge of Engagement Via Social Media - Muhammad Rudi Syahputra; Tasrizal Tasrizal; Muksalmina Muksalmina; Muhammad Muhammad; Khairul Amri Ismail (FASYA Press, 2026)
This article explores the legal status of khitbah (engagement) conducted through social media platforms, particularly Facebook, in light of Shafi”˜i jurisprudence. In classical Islamic law, khitbah represents a preliminary stage of marriage, intended to establish mutual understanding and commitment prior to the solemnization of the marriage contract (”˜aqd al-nikÄá¸¥). Traditionally, this practice has been carried out in face-to-face settings, mediated by families and community norms. However, the rapid development of communication technology has reconfigured modes of social interaction among Muslims, including those related to religiously significant practices such as khitbah. The study employs a qualitative library research approach, drawing upon primary Shafi”˜i fiqh sources such as MughnÄ« al-Muá¸¥tÄj (al-Khaá¹Ä«b al-ShirbÄ«nÄ«), I”˜Änat al-á¹¬ÄlibÄ«n (al-Shaá¹Ä), and al-Fiqh al-IslÄmÄ« wa Adillatuh (al-Zuá¸¥aylÄ«), alongside contemporary scholarly debates in Islamic family law and digital communication studies. The findings demonstrate that a khitbah performed through social media is legally valid, since the principle al-kitÄbah ka-l-khiá¹Äb that written communication is equivalent to spoken communication is well established in Islamic jurisprudence. Thus, proposals made through text messages, social media posts, or digital calls fulfill the requirement of explicit (á¹£arÄ«á¸¥) or indirect (ta”˜rÄ«á¸) expression of intent. Nonetheless, while the legality of such practice is affirmed, ethical and social concerns remain paramount. The potential for deception, anonymity, and digital intimacy presents significant challenges that demand moral vigilance. Islamic ethics emphasizes safeguarding honor (”˜ird) and preventing harm (dharar), necessitating caution in applying classical rulings to modern contexts. The study concludes that social media-based khitbah reflects the adaptability of Islamic jurisprudence to new technological realities, while also underlining the importance of ethical discipline in digital religious practices.